Burger Mok / Muhammad Daniel Rahmat ... [et al.] - Rahmat, Muhammad Daniel; Mohaini, Ali Imran; Mohd Isnin, Muhammad Shamsul Bahri; Herman, Aiman Amanda Syahirah; Daud, Shafwatunnur (2021)
Our business has been registered as "Burger Mok". BurgerMok is a widely developed online business. The business was built by a Bachelor of Arts student in Culinary Arts. So, they decided to go out with fast food which is BurgerMok. The business idea of ​​the food truck and delivery is based on their own experience and get the idea while they are learning. Because this burger food is very popular with many people and because of that, their own ideas in producing their own burgers arose. Like other businesses, BurgerMok also cannot escape challenges in their day -to -day business operations. Healthy Food does not have an effective marketing strategy however, they are very confident that this BurgerMok business can be expanded widely if it has the right marketing and tactics.